Perancangan Sistem Informasi Kehadiran Siswa Berbasis Web dan SMS GateWay Menggunakan Metode Waterfall - Akbar, Fajar; Susafa'ati, Susafa'ati (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2019)
Â Abstract - The student attendance system that is used today by high school IP. YAKIN Jakarta today still uses the attendance system manually, in the form of registration on paper, that is, using attendance attendance books so that students often experience errors in the student attendance calculation process. For that information systems are needed in the form of applications that can help in the process of doing attendance to students. So this article presents the process of designing a web-based student attendance information system with an SMS gateway in high school IP. YAKIN Jakarta. With this application it can make it easier for teachers to do attendance to students, making it easier for teachers to do the process of calculating student attendance and making it easier for parents to supervise students while at school. Â Abstrak - Sistem kehadiran siswa yang di pakai saat ini oleh SMA IP. YAKIN Jakarta saat ini masi menggunakan sistem absensi secara manual, berupa pencatataan di kertas, yaitu menggunakan buku absensi kehadiran siswa sehingga sering adanya kesalahan dalam proses perhitungan absensi siswa. Untuk itu dibutuhkan sistem informasi berupa aplikasi yang dapat membantu dalam proses melakukan absensi kepada siswa. Maka artikel ini menyajikan proses Perancangan Sistem Informasi Kehadiran Siswa Berbasis Web Dengan SMS Gateway Pada SMA IP. YAKIN Jakarta. Dengan adanya aplikasi iniÂ dapat memepermudah guru untuk melakukan absensi pada siswa, mempermudah guru untuk melakukan proses perhitungan absensi siswa dan mempermudah orang tua dalam mengawasi siswa selama di sekolah.Keywords: PHP, MySql, Sms Gateway, Information System, Student Attendance.